Estimates of the Output Gap in Armenia with Applications to Monetary and Fiscal Policy. (IMF Working Papers; Working Paper, 2010)
This paper employs several econometric techniques to estimate the Armenian output gap. The findings indicate that the output gap is significantly positive in 2007 and 2008 and decreased dramatically in 2009. The paper uses these results to estimate a New Keynesian Phillips curve for Armenia, suggesting a significant role of the output gap and inflation expectations in determining current inflation. Finally, the underlying fiscal stance over the period 2000-09 is assessed by estimating the cyclically-adjusted fiscal balance. Most of Armenia's fiscal deficit is found to be structural. Fiscal policy, while providing counter-cyclical support in 2009, has been largely pro-cyclical in the past.